America the Indispensable Power: Singapore's Perspective of America as a Security Partner. Issue 1 (16th January 2016) - Tan, See Seng
Abstract : Security relations between Singapore and the United States have evolved significantly since the former gained independence in 1965. From an unlikely partnership pursued by Singapore by default rather than choice during Singapore's formative years, the United States has since evolved into a vital partner of Singapore because of the indispensable role it has played in ensuring a stable balance of power in the Asia‐Pacific and in facilitating the economic prosperity of the region. Their partnership has endured rough patches due to political differences. In the post‐9/11 period, Singapore's security has also been affected as a result of its close ties with the United States. Moreover, Singapore's reliance on hedging has at times fostered doubts—more so now in the era of U.S. rebalancing—about the congruence of its interests with those of America. However, it is clear Singapore prefers the perceived benign presence of the United States over other powers.